2022
DOI: 10.1002/adom.202102776
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Optical Imaging of In‐Plane Anisotropy in Two‐Dimensional SnS

Abstract: Two‐dimensional (2D) tin(II) sulfide (SnS) crystals belong to a class of orthorhombic semiconducting materials with remarkable properties, such as in‐plane anisotropic optical and electronic response, and multiferroic nature. The 2D SnS crystals exhibit anisotropic response along the in‐plane armchair (AC) and zigzag (ZZ) crystallographic directions, offering an additional degree of freedom in manipulating their behavior. Here, advantage of the lack of inversion symmetry of the 2D SnS crystal, that produces se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…It is observed that the shape of the polar-diagrams changes for different nanosheets, which is the signature of differences in their in-plane anisotropy. [67] X-ray photoelectron spectroscopy (XPS) measurements were carried out to investigate the chemical states and stoichiometry of the isolated SnS nanosheets. Figure S6, Supporting Information presents the Sn3d and S2p core level spectra of the isolated FL-SnS sheets, confirming the high purity of isolated SnS crystals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that the shape of the polar-diagrams changes for different nanosheets, which is the signature of differences in their in-plane anisotropy. [67] X-ray photoelectron spectroscopy (XPS) measurements were carried out to investigate the chemical states and stoichiometry of the isolated SnS nanosheets. Figure S6, Supporting Information presents the Sn3d and S2p core level spectra of the isolated FL-SnS sheets, confirming the high purity of isolated SnS crystals.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, here the in‐plane structural anisotropy of the exfoliated crystals is explored by polarized second harmonic generation (P‐SHG). [ 67 ] In Figure 2h, we present the sum of the P‐SHG intensity images, obtained from different SnS crystals belonging to the same field of view, for all orientations of the excitation linear polarization φ . It is observed that the shape of the polar‐diagrams changes for different nanosheets, which is the signature of differences in their in‐plane anisotropy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional (2D) materials consisting of atomically thin sheets with covalent intralayer bonding and van der Waals interlayer bonding have attracted significant attention due to their fascinating physicochemical properties. , Shaping 2D materials into one-dimensional (1D) nanoribbons is one of the effective strategies for tuning or enhancing their electronic, magnetic, and optical properties as a result of the large aspect ratio, quantum confinement, and edge effect, enabling their applications in multidisciplinary areas such as photodetectors, sensing, field emission, energy storage, and catalysis. As one important class of 2D materials, layered group IV–VIA monochalcogenides (e.g., SnS, SnSe, GeSe, and GeS) are recognized as analogues of phosphorene with buckled structures, which give rise to their structural anisotropy manifested in the Raman response, nonlinear optical property, electrical mobility, and photoactivity. Of particular interest, SnS is a p-type semiconductor with a sizable bandgap, and few-layer SnS exhibits desirable electronic and optoelectronic properties such as a large absorption coefficient, tunable electrical conductivity, and high carrier mobility. Moreover, SnS is chemically stable, abundant on Earth, and nontoxic. , These advantageous features render SnS a promising candidate to be employed in various applications such as photodetectors, photovoltaic cells, and field-effect transistors …”
mentioning
confidence: 99%
“…Recently, Luan et al reported the real-time observation of an anisotropic exciton–polariton in an SnS waveguide . Maragkakis et al demonstrated polarization-resolved second harmonic generation imaging of in-plane anisotropy in a layered SnS crystal . Alberding et al investigated the ultrafast optical response of a nano- to micrometer-sized SnS film with transient terahertz spectroscopy, in which the carrier mobility and carrier dynamics of the thin films exhibit the strong particle size dependence .…”
mentioning
confidence: 99%